2008
DOI: 10.1111/j.1460-9568.2008.06123.x
|View full text |Cite
|
Sign up to set email alerts
|

Odor vapor pressure and quality modulate local field potential oscillatory patterns in the olfactory bulb of the anesthetized rat

Abstract: A central question in chemical senses is the way that odorant molecules are represented in the brain. To date, many studies, when taken together, suggest that structural features of the molecules are represented through a spatio-temporal pattern of activation in the olfactory bulb (OB), in both glomerular and mitral cell layers. Mitral/tufted cells interact with a large population of inhibitory interneurons resulting in a temporal patterning of bulbar local field potential (LFP) activity. We investigated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 40 publications
(40 reference statements)
8
54
0
1
Order By: Relevance
“…We hypothesized that odor information in the OTs of awake rats is represented by changes in LFP spectral power. This straightforward hypothesis follows suit with known aspects of odorevoked LFP activity in the OB and piriform cortex, with each displaying increases in spectral power during odor inhalation (e.g., Buonviso et al 2003;Cenier et al 2008;Chapuis et al 2009;Freeman and Baird 1987;Kay and Beshel 2010). In addition, this hypothesis agrees with the prominent recruitment of neurons within the OT upon odor presentation (Carlson et al 2013;Payton et al 2012;Rampin et al 2012).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…We hypothesized that odor information in the OTs of awake rats is represented by changes in LFP spectral power. This straightforward hypothesis follows suit with known aspects of odorevoked LFP activity in the OB and piriform cortex, with each displaying increases in spectral power during odor inhalation (e.g., Buonviso et al 2003;Cenier et al 2008;Chapuis et al 2009;Freeman and Baird 1987;Kay and Beshel 2010). In addition, this hypothesis agrees with the prominent recruitment of neurons within the OT upon odor presentation (Carlson et al 2013;Payton et al 2012;Rampin et al 2012).…”
Section: Discussionsupporting
confidence: 57%
“…In addition, this hypothesis agrees with the prominent recruitment of neurons within the OT upon odor presentation (Carlson et al 2013;Payton et al 2012;Rampin et al 2012). Among the spectral bands that have received the most attention in terms of being shaped by odor and odor quality, are beta and gamma (Cenier et al 2008;Lepousez and Lledo 2013;Lowry and Kay 2007;Martin et al 2006Martin et al , 2007. We found that the OT is also characterized by considerable beta-band power and detectable, yet minor, gamma-band power.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, this range includes TMT, a component of fox feces, and toluene. In urethane anesthetized rats, similar observations were made that the molecular feature of odorants influenced the probability of emergence of beta oscillations (Cenier et al, 2008). Consequently, the reason why some odorants elicited higher beta power could be due to their volatility rather than their innate value.…”
Section: Odor-evoked Modulation Of Lfps Influences On Beta and Gammamentioning
confidence: 53%
“…This transformation leads, for each trial, to a time frequency matrix where each point represents the level of energy for a given instant and a given frequency: hot color spots represent transitory oscillations. The method used to quantify changes in the beta (15-40 Hz) frequency band is based on the wavelet ridge extraction previously described by Roux et al (2007) and applied to biological signals by Cenier et al (2008). For each trial, a power threshold (mean ϩ 3 STD) was calculated between 15 and 40 Hz on the baseline period.…”
Section: Lfp Analysismentioning
confidence: 99%